Optimizing Ammonia Removal in Recirculating Aquaculture Systems Using NaOH-Activated Sugarcane Bagasse Carbon - Said Ali Akbar; Cut Nuzlia; Muhammad Hasan; Zulkarnain Jalil; Ilham Zulfahmi (Science & Technology Asia, 2025)
This study evaluates the effectiveness of activated carbon produced from sugarcane bagasse as an ammonium filter in a Recirculating Aquaculture System (RAS) for Nile tilapia (Oreochromis niloticus). The research involved five different treatments with varying amounts of carbon mass. The results indicated that the highest carbon mass treatment (P5) achieved superior water quality and fish growth performance, including a specific growth rate (SGR) of 3.345% per day, the lowest feed conversion ratio (FCR) of 0.829, and a 100% survival rate. Fourier Transform Infrared (FTIR) and Scanning Electron Microscope (SEM) analyses confirmed significant pore enlargement and the presence of functional groups facilitating ammonium adsorption. The findings demonstrate the potential of sugarcane bagassederived activated carbon as a sustainable and cost-effective solution for improving water quality and promoting fish growth in aquaculture systems.